(untitled) (International Seven Journal of Health Research, 2023)
Introduction: Osteoporosis is one of the main public health problems affecting the elderly (over 60 years of age). It is characterized by a reduction in bone mineral density (BMD) together with a deterioration in the microarchitecture of bone tissue, which leads to increased skeletal fragility and the likelihood and risk of fractures. Objective: The aim of this study was to analyze the bone density of women aged between 60 and 70 referred to the bone densiometry department of a clinic in the Mucuri valley, in Nanuque (MG). Methodology: The research used in this study is classified as documentary research because it aims to analyze bone density in a group of women aged 60 to 70 who underwent bone densiometry at a clinic in Nanuque Minas Gerais. Results: In addition, it is worth noting that one third of women aged sixty-five have osteoporosis and 50% of women over 75 have been diagnosed with this pathology, i.e. assessing the patient’s age is fundamental for analyzing the diagnosis, treatment and evolution of the pathology Conclusion: After the end of the study carried out in the city of Nanuque, it was identified that the objectives of the article were achieved, since it was possible to analyze the bone density of women in the age group of 60 to 70 years in this municipality, also, the age group, the diagnosis after the result of the examination and the ethnicity were identified.